Stella Spantidaki. Textile Production in Classical Athens. - Llewellyn-Jones, Lloyd (Journal of Greek Archaeology, 2017)
Studies of ancient dress continue, I am pleased to observe, to grow apace. In the past year alone I can think of close to a dozen publication that have dealt with the production, wearing, or meaning of clothing in Classical antiquity and I’m alerted to the fact that we can expect more in the near future. This is very pleasing given that some eighteen years ago I organized an international conference on the theme of women’s dress in the ancient Greek world in which I highlighted what I conceived to be the plight of ancient dress-studies – which was certainly true then for Greek dress (work on Roman costume was faring better at the time).